Enhancing Infant Mental Health Using a Capacity-Building Model: A Case Study of a Process Evaluation of the Ready, Steady, Grow Initiative. Issue 4 (October 2017) - O'Farrelly, Christine; Lovett, Judy; Guerin, Suzanne; Doyle, Orla; Victory, Gerard
Abstract : Infant mental health (IMH) is best promoted through a continuum of services underpinned by strong service capacity. However, service providers often lack fundamental IMH knowledge and skills. Using the Ready, Steady, Grow (RSG) initiative as a case study of a capacity-building model (P., Hawe, L., King, M., Noort, C., Jordens, & B., Llyod, 2000 ), this article contributes to the field by investigating the facilitators and challenges to IMH promotion in a disadvantaged community in Ireland. A mixed-methods study assessed the degree to which RSG has developed the local service community capacity. Data included semistructured interviews ( n = 23) and a survey with service stakeholders from nursing, speech and language, early childhood care and education, social work, family support, physiotherapy, and youth work ( n = 40). The findings indicated that RSG has enhanced IMH capacity among service stakeholders by establishing a strong groundwork and enthusiasm for IMH, in addition to building preliminary IMH skills, although scope remains for further engagement and training. Ongoing barriers to capacity building include a dearth of resources and concern about sustainability. This case study offers theoretical and practical insights to those interested in promoting child health using a capacity-building model. Abstract : Supplemental Digital Content is Available in the Text.